Il dono di Keynes per l’ordine economico internazionale - Cedrini, Mario (EtnoAntropologia, 2014)
The rediscovery, in the times of the crisis, of John Maynard Keynes’s proposals for postwar reform of the international economic order invites historians of economic thought to clarify the purposes of Keynes’s international diplomacy. Drawing on categories borrowed from the sociological and anthropological literatures (particularly the gift), the article proposes an original, interdisciplinary view of Keynes’s diplomacy, allowing a revival of Keynes’s peculiar vision of the complexity of international economic relations for the analysis of the current global and European economic disorder.